Water Repellency in Hydrophobic Nanocapsules—Molecular View on Dewetting. Issue 22 (29th April 2014) - Müller, Achim; Garai, Somenath; Schäffer, Christian; Merca, Alice; Bögge, Hartmut; Al‐Karawi, Ahmed Jasim M.; Prasad, Thazhe Kootteri
Abstract Invited for the cover of this issue is the group of Achim Müller at the University of Bielefeld. The image (including artwork from Hartmut Bögge) depicts manifestations of the ubiquitous hydrophobic effects which play a crucial role in general biology, for example, the so‐called "self‐cleaning properties" of the Lotus leaves (model shown), in structural biology and for many practical applications in daily life. The new results refer to synthetic hydrophobic nanocapsules in which encapsulated water is repelled from the inner wall (left), in sharp contrast to the situation found in related hydrophilic capsules (right). Read the full text of the article at 10.1002/chem.201402216.